Understanding inflation dynamics: Where do we stand? - Maarten Dossche (National Bank of Belgium, 2009)
I summarize recent progress made in the literature on inflation dynamics. This has been a very productive area of research due to the development of the so-called New Keynesian model and the availability of new macroeconomic and microeconomic evidence. Nevertheless, a number of problems still subsist. In particular the importance of temporary price markdowns to inflation dynamics and the characteristics of the information set price-setters use for their price adjustment decision currently constitute unresolved issues
Keywords: E30; E50; E60; 330; Inflation dynamics; New Keynesian model; sticky prices; Inflationstheorie; Dynamisches Gleichgewicht; Preisrigidität; Theorie